2020
DOI: 10.3390/su12083137
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Structural Features and Influential Factors of the Spatial Network of China’s Regional Ecological Efficiency Spillover

Abstract: A regional coordinated development strategy is an important measure that is often used to implement sustainable development in China. However, many obstacles greatly limit the realization of regional ecological coordinated sustainable development. In this paper, ecological efficiency is utilized as an important indicator of sustainable development, and the network analysis method is used to explore the spatial correlation relationship of regional ecological coordinated sustainable development. This paper calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…(2) Both digital financial technology and urban ecological efficiency have significant spatial spillover effects; that is, digital financial technology and urban ecological efficiency of surrounding cities promote local digital financial technology and urban ecological efficiency, respectively. This is not only consistent with the research results of Shen et al on the spatial distribution of digital financial indices [33], but also consistent with the research results of Xu et al on the ecological efficiency spatial spillover [8]. (3) Digital financial technology of surrounding cities has an inhibitory effect on the ecological efficiency of local cities, and the improvement of the ecological efficiency of surrounding cities has a siphon effect on the local digital financial technology.…”
Section: Theoretical Frameworksupporting
confidence: 90%
See 2 more Smart Citations
“…(2) Both digital financial technology and urban ecological efficiency have significant spatial spillover effects; that is, digital financial technology and urban ecological efficiency of surrounding cities promote local digital financial technology and urban ecological efficiency, respectively. This is not only consistent with the research results of Shen et al on the spatial distribution of digital financial indices [33], but also consistent with the research results of Xu et al on the ecological efficiency spatial spillover [8]. (3) Digital financial technology of surrounding cities has an inhibitory effect on the ecological efficiency of local cities, and the improvement of the ecological efficiency of surrounding cities has a siphon effect on the local digital financial technology.…”
Section: Theoretical Frameworksupporting
confidence: 90%
“…From the perspective of spatial dimension, the differences of regional development foundation and environment, together with the guidance of the development mode "From points to areas; parts pushing the whole", make spatial heterogeneity the characteristic fact of digital financial technology and green development, which is manifested as the spatial agglomeration of digital financial technology and ecological efficiency [7,8]. However, the spatial interaction spillover effect between the two has not been paid much attention by the researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai and other scholars used the spatial analysis method to analyze the spatial-temporal pattern and power of the coupling and coordinated development of new urbanization and agricultural ecological environment in detail [ 8 ]. In 2020, Xu's team used the network analysis method to explore the spatial correlation of regional ecological coordinated sustainable development; found that industrial structure, economic development, and geographical proximity have a positive impact on the spatial spillover of regional ecological efficiency; and put forward corresponding policies [ 9 ]. Based on 99 typical coastal plain counties in Jiangsu Province, Xiong et al optimized and regulated regional urban development imbalance from multiple perspectives [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large number of studies are based on the geographical effect of regional green total factor pro-ductivity (mainly with the DEA model). The Xu et al research found that the network of ecological profit distribution in the region presents a characteristic core-edge construction, and there is an obvious graded construction between parts with different orientations and roles [32]. The regional ecological efficiency of China is in the process of long-term fluctuation, but it is generally improved, with noticeable regional differences and widening gaps [33].…”
Section: Literature Review and Contributionmentioning
confidence: 99%